Uneven Evolutions - Kristen Guest (Humanimalia, 2023)
Mackenzie Cooley. The Perfection of Nature: Animals, Breeding, and Race in the Renaissance. Chicago: University of Chicago Press, 2022. xvi + 353 pp., 30 halftones. $37.50 (pb), $112.50 (hb), $36.99 (pdf).